2018
DOI: 10.1037/ccp0000347
|View full text |Cite
|
Sign up to set email alerts
|

A randomized control trial of a deviance regulation theory intervention to increase alcohol protective strategies.

Abstract: OBJECTIVE: Normative feedback remains an effective approach to reducing alcohol use among college students. However, this approach is difficult to extend to protective behavioral strategies (PBS), which are proximal to alcohol-related problems. Deviance Regulation Theory (DRT) is a social psychology theory that posits individuals choose engage in behaviors to standout out in positive ways or avoid standing out in negative ways. The current study tests a DRT-based randomized control trial. METHOD: College stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 45 publications
1
31
1
9
Order By: Relevance
“…DRT has been shown to increase PBS use and subsequently decrease alcohol consumption and alcohol consequences in college student drinkers (Dvorak et al, 2017;Dvorak et al, 2015;Dvorak, Troop-Gordon, et al, 2018;Sargent et al, 2018). This has been observed both in regular drinking environments (Dvorak et al, 2015;Dvorak, Troop-Gordon, et al, 2018), as well as unique environments such as during Spring Break (Dvorak et al, 2017;Sargent et al, 2018).…”
Section: Deviance Regulation Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…DRT has been shown to increase PBS use and subsequently decrease alcohol consumption and alcohol consequences in college student drinkers (Dvorak et al, 2017;Dvorak et al, 2015;Dvorak, Troop-Gordon, et al, 2018;Sargent et al, 2018). This has been observed both in regular drinking environments (Dvorak et al, 2015;Dvorak, Troop-Gordon, et al, 2018), as well as unique environments such as during Spring Break (Dvorak et al, 2017;Sargent et al, 2018).…”
Section: Deviance Regulation Theorymentioning
confidence: 99%
“…Social norming highlights pressures students might feel to "fit in" at school, and the value of a norm debiasing intervention is that it works off that existing motive so that "fitting in" transforms from a desire to drink heavily and irresponsibly to a desire to drink in moderation and responsibly. But, college students are also motivated by the desire to "stand out" and this motive can also influence alcohol-related decisions Dvorak et al, 2017;Dvorak et al, 2016;Dvorak et al, 2015;Dvorak, Troop-Gordon, et al, 2018). Indeed, Ferrer and colleagues (2012) have shown that transitions in drinking among FTIC students may hinge on their need to differentiate themselves from the social norm.…”
Section: Norm-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…DRT is a social psychology theory which posits that individuals will strive to "stand-out" in desirable ways or to "fit-in" to avoid deviating from social norms in undesirable ways, as a way to maintain a desired self-image (15). DRT has been most utilized to target substance use behaviors (16,17). However, DRT has been used to target various other health behaviors including, unsafe driving (18), risk-taking (19), flu immunizations, and condom use (15).…”
Section: Deviance Regulation Theorymentioning
confidence: 99%
“…Since this early work, a series of studies by Dvorak and colleagues have tested the effects of DRTbased interventions on substance use behaviors and found it has utility (Dvorak et al, 2017;Dvorak et al, 2016;Dvorak et al, 2015;Dvorak, Troop-Gordon, et al, 2018;Sargent et al, 2018).…”
Section: Deviance Regulation Theorymentioning
confidence: 99%